Feeding behavior of male cattle under restricted grazing, supplemented with distiller maize grains during the dry period - Iraola, Jorge; Mu?oz, E.; Garc?a Orta, Yenny; Garc?a, Yoleisy; Hern?ndez, Jorge Luis; Tuero, O.; Moreira, Onidia (Cuban Journal of Agricultural Science, 2013)
?Feeding ability and productive yield was evaluated in male cattle under restricted grazing for 90 days during the dry period. Twenty four animals (commercial Zebu) were used with a mean live weight of 359.24 ? 1.09 kg, grazing in 20 ha with different supplementation levels. A completely randomized design was applied with the following treatments: I) grazing, II) grazing plus 1.5 kg of distiller maize grains (DDGS), III) grazing plus 2.5 kg DDGS. The activities: ingestion, rumination, rest, water intake and inactivity were analyzed. The frequency of the activities between each hour of the day and average daily gain (ADG) were determined. Data were processed with INFOSTAT and through ComparPro version I. In treatment I animals devoted more time (P < 0.001) to ingestion and less (P < 0.001) to rumination regarding the remaining activities (6.88; 5.73 and 5.09 h and 0.58; 0.99 and 1.28 h) for ingestion and rumination in treatments I, II and III, respectively. The ingestion frequency of pastures showed between 8:00 and 9:00 a.m. higher (P < 0.001) a ount of animals grazing. Treatment I (71 %) was superior by 9 and 21 % to treatments II and III, respectively. ADG was conditioned by the supplementation level. The use of DDGS decreased the ingestion time, increased rumination and improved ADG in the treatment with the highest supplementation level. Key words: beef cattle, feeding ability, distiller maize grains